2018
DOI: 10.24198/kultivasi.v17i1.15668
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfatan andaliman (Zanthoxylum acanthopodium DC) sebagai tanaman penghasil minyak atsiri

Abstract: Andaliman (Zanthoxylum acanthopodium DC) is one of the most widely used herbs in Toba Samosir and North Tapanuli, North Sumatera, at an altitude of 1,500 m asl, found growing wild in the Tapanuli area and used as spices in traditional Batak Angkola and Batak Mandailing. Beside North Sumatra, andaliman belonging to the family Rutaceae (family of oranges) is also found in India, China, and Tibet. This study was aimed to study the role of andaliman plants as a source of essential oils. Research method used was li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
0
9
0
8
Order By: Relevance
“…inhibiting the expression of several biomarkers of inflammation at the level of protein synthesis (tumor necrosis factor-alpha [TNF-α], protein cyclooxygenase [COX-2], and matrix metallopeptidase-9 [MMP-9]) and gene (TNF-α, IL-6, iNOS, COX-2, and MMP-9) against the macrophage that was induced by lipopolysaccharide [16]. Meanwhile, several studies reported the antimicrobial activity of lemon pepper against some pathogens such as Staphylococcus aureus, Escherichia coli, Bacillus cereus, Bacillus stearothermophilus, Pseudomonas aeruginosa, Vibrio cholera, and Salmonella typhimurium through in vitro study [17][18][19][20].…”
Section: Purnama Et Almentioning
confidence: 99%
“…inhibiting the expression of several biomarkers of inflammation at the level of protein synthesis (tumor necrosis factor-alpha [TNF-α], protein cyclooxygenase [COX-2], and matrix metallopeptidase-9 [MMP-9]) and gene (TNF-α, IL-6, iNOS, COX-2, and MMP-9) against the macrophage that was induced by lipopolysaccharide [16]. Meanwhile, several studies reported the antimicrobial activity of lemon pepper against some pathogens such as Staphylococcus aureus, Escherichia coli, Bacillus cereus, Bacillus stearothermophilus, Pseudomonas aeruginosa, Vibrio cholera, and Salmonella typhimurium through in vitro study [17][18][19][20].…”
Section: Purnama Et Almentioning
confidence: 99%
“…Selama ini pemanfaatan biji andaliman pada umumnya masih dilakukan untuk memenuhi kebutuhan konsumsi rumah tangga sebagai bumbu masak bagi masyarakat di Kawasan Danau Toba dan masyarakat perantau yang berasal dari Kawasan Danau Toba di kota-kota besar di Indonesia. Pemanfaatan andaliman secara komersil juga masih terbatas sebagai bumbu rempah penguat rasa kuliner khas Batak, seperti ikan mas arsik, natinombur, dan sangsang yang disajikan langsung melalui restoran khas Batak di sekitar Kawasan Danau Toba [9]. Biji andaliman mengandung senyawa aromatik dengan rasa pedas dan getir yang khas, dan hangat.…”
Section: Pendahuluanunclassified
“…Di Indonesia tumbuhan dikenal masyarakat dengan nama andaliman dan dimanfaatkan sebagai rempah dalam masakan. Bumbu andalaiman memberi rasa pedas dan aroma yang khas terutama dalam masakan gulai ikan [1].…”
Section: Submitted: 26 Februari 2019unclassified
“…Tujuan penelitian ini, mengisolasi senyawa alkaloid furokuinolin yang terdapat dalam kulit batang Z. acanthopodium DC. Dua senyawa alkaloid furokuinolin, diktammin (1)…”
Section: Jurnal Sains Dan Kesehatanunclassified